The Assessment of Servant Leadership and Inovation in Aircraft Services Strategic Business Unit PT Dirgantara Indonesia - Nugroho, Raden Cahyo Adhi; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
Abstract.This thesis is conducted to measure servant leadership and novation in Aircraft Services Strategic Business Unit PT Dirgantara Indonesia. This analysis is conducted based on leader distrust and company performance phenomena. This research is a quantitative research with causal explanatory method. Based on the hypothesis testing results, it is proven that servant leadership has significance and positive influence on inovation in Aircraft Services Strategic Business Unit PT Dirgantara Indonesia. Managerial implications that can be done is management is expected to listen, be humble, more appreciate to the performance of employees, more accomodating any input, and more flexible in aligning activities in order to improve inovation thus at the end helps company to achieve its goals. Finally, high inovation is a reflection of companys good performance.Keywords: Servant leadership, Inovation, PT Dirgantara Indonesia.